Human Development Strategy Welcomes the Peak of the Demographic Bonus in Indonesia - Suardana, I Ketut; Satriawan, Dewa Gede (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to elaborate the human development strategy towards the peak of demographic bonuses in Indonesia. The specific objectives of this study were to analyze (1) the number and population growth in Denpasar City, Bali Province; and (2) employment opportunities and challenges in Denpasar City, Bali Province.This study fully uses secondary data collected from various publications. The data analysis was descriptive where the relationships between variables are carried out with a descriptive approach. The study result indicates that bonus demographics will occur in the range of 2015-2025 inthe Denpasar City, because population growth continues to increase and the share of the productive age population is also more dominant than the non-productive population. However, the level of preparation in the labor sector has so far not been optimal. These conditions threaten Denpasar City can not reach the benefits of this window of opportunity.This is due to still unemployment in the Denpasar City.